Eating high fat chow increases the sensitivity of rats to 8-OH-DPAT-induced lower lip retraction - Li, Jun-Xu (2011)
Eating high fat food can alter sensitivity to drugs acting on dopamine systems; this study examined whether eating high fat food alters sensitivity to a drug acting on serotonin (5-HT) systems. Sensitivity to (+)-8-hydroxy-2-(dipropylamino) tetralin hydrobromide (8-OH-DPAT; 5-HT(1A) receptor agonist)-induced lower lip retraction was examined in separate groups (n=8-9) of rats with free access to standard (5.7% fat) or high fat (34.3% fat) chow; sensitivity to quinpirole (dopamine D(3)/D(2) receptor agonist)-induced yawning was also examined. Rats eating high fat chow gained more body weight than rats eating standard chow and, after 6 weeks of eating high fat chow, they were more sensitive to 8-OH-DPAT (0.01-0.1 mg/kg)-induced lower lip retraction and quinpirole (0.0032-0.32 mg/kg)-induced yawning. These changes were not reversed when rats that previously ate high fat chow were switched to eating standard chow and sensitivity to 8-OH-DPAT and quinpirole increased when rats that previously ate standard chow ate high fat chow. These data extend previous results showing changes in sensitivity to drugs acting on dopamine systems in animals eating high fat chow to a drug acting at 5-HT(1A) receptors and they provide support for the notion that eating certain foods impacts sensitivity to drugs acting on monoamine systems.